Socialization of Buginese Language E-learning Application with Lontara Script Translation Feature at SMPN 2 Pangkajene - Nurtanio, Ingrid; Yohannes, Christoforus; Bustamin, Anugrayani; Mokobombang, Novy Nur R A; Areni, Intan Sari; Tahir, Zulkifli; Adnan, Adnan; Marindah, Tyanita Puti; Paundu, Ady Wahyudi; Nurdin, Arliyanti; Musyfirah, Kamtina; Hikmah, Nur; Mahdaniar, Mahdaniar (Faculty of Engineering UNHAS, 2024)
Preservation of indigenous languages, especially Bugis with Lontara script, is an important challenge in the digital era. In school activities, mastery and learning of local languages ​​are associated with one subject, namely Muatan Lokal. However, the main problem that is often encountered is the use of indigenous languages ​​that are increasingly minimally socialized, thus reducing students' interest and motivation in learning this local language, especially in SMP Negeri 2 Pangkajene Class VII. This community service aims to be a forum for socializing research results in the Department of Informatics and Electrical Engineering, Hasanuddin University in the form of an E-learning application that facilitates interactive learning of Bugis with Lontara script. In addition, this activity is expected to contribute to the advancement of knowledge and technology by providing E-learning tools, in the form of mobile applications, to support learning both at school and at home. The process of introducing this application involves quantitative analysis in the form of an initial survey (pre-test) which includes the user experience (in this case students) when learning Bugis and then ends with a final survey (post-test) and System Usability Scale (SUS) testing to determine the student's experience when using this Bugis language application. The results obtained indicate the formation of Bugis language learning motivation after participants are familiar with this E-learning application with an increase of 52% from 32% less motivated to 84% very motivated. In addition, this Bugis language E-learning application also reached an acceptable level based on SUS with a value of 74.